Spontaneous coronary artery dissection (SCAD): about 2 cases - Elkasimi, Abdelouahab; Elouazzani, Ghizlane; Hbali, Anas; Ismaili, Nabila; Elouafi, Nouha (The Pan African medical journal, 2017)
Spontaneous coronary artery dissection (SCAD) is a rare cause of acute coronary syndrome (ACS); its prevalence is estimated to be less than 3%. It is defined as a separation within the coronary arterial wall secondary to intramural bleeding with or without intimal tear, creating a false channel. It mainly affects young subjects, mainly women, without coronary atherosclerosis or risk factors for atherosclerosis. However, the occurrence of spontaneous dissection due to atheromatous disease is possible. We here report 2 cases of spontaneous coronary dissection, in order to discuss its pathogenesis, factors favoring its occurrence, its clinical presentation and its therapeutic management.